Effect of lentivirus-mediated gene silencing, targeting toll-like receptor 2, on corneal allograft transplantation in rats. (November 2017) - Bai, Lang; Liang, Weiyi; Chen, Minting; Cissé, Yacouba; Liu, Jing; Su, Yaru; Yu, Jian; Liu, Qiong
Highlights: TLR2/MyD88 signaling pathway may play a critical role in cornea transplantation. TLR2 siRNA could safely and effectively suppress TLR2 expression on cornea. Gene silencing targeting TLR2 could attenuate rejection after keratoplasty. Abstract: Aim: The present work aims to assess the effectiveness of lentiviral vector (LV) mediated Toll-like receptor 2 (TLR2) gene silencing in the survival of transplanted corneal allografts, against immune rejection, in rats. Methods: LV mediated TLR2 small interference RNA (SiRNA) with enhanced green fluorescent protein (eGFP) [LV-TLR2-siRNA-eGFP] was realised and transfected to both rat corneal epithelial (EC) and stromal cells (SC). Multiplicity of infection (MOI) was optimized for transfection efficiency using flow cytometric (FCM) analysis. Viability of transfected cells and the success rate of TLR2 gene silencing were respectively determined by CCK-8 assay and western blot assay. The in-vivo experiments were subjected to a penetrating keratoplasty (PK) performed between host Sprague Dawley (SD) and donor Wistar/SD rats, randomly dividing them into 4 groups including the allograft, isograft, allograft treated with LV-eGFP (LV blank control) and allograft treated with LV-TLR2-siRNA-eGFP (LV treated group). The rejection index (RI) was then recorded under a slit lamp, every day following surgery. Expression of the TLR2 and Myeloid differentiation primary response gene 88 (MyD88) were detected by using immunohistochemistry on day 9 post-surgery, whereas grafts's TLR2 and MyD88 mRNA were determined on day 5, 9, and 14 post-surgery performing RT-PCR and, normal rat corneas were included as additional controls. Results: Transfected cells showed the strongest eGFP expression when MOI was 200 with an efficiency of 77.5% for EC and 76.3% for SC. CCK-8 assay, as measured at 72 and 96 h post transfection, showed no significant changes in the cell viability (both EC and SC) between the transfected and the control group ( p  > 0.05, p  > 0.05). Western blot results demonstrated a successful down regulation of TLR2 expression by LV-TLR2-SiRNA-eGFP, in both EC and SC. In vivo, compared to allograft group, LV treated group demonstrated less edema, opacity and neovascularization. Immunohistochemical analysis revealed a lower expression of TLR2 and MyD88 in isograft and LV treated group as compared to allograft group. TLR2 and MyD88 mRNA were detected in all grafts, and increased over time. With its highest expression in allograft group (peak on day 9), the mRNA expression for TLR2 and MyD88 showed a significant difference amongst the groups, on both day 9 and 14 (p < 0.001). Conclusions: LV mediated TLR2 siRNA could effectively down regulate the TLR2 expression via RNA interference and prolong the survival of corneal grafts, although not necessarily able to prevent the rejection.